BIOINDICADORES COMO HERRAMIENTAS PARA LA EVALUACIÓN DE LA CONTAMINACIÓN AMBIENTAL - Luna Bautista, Carlos Felipe; Gómez-Otamend, Edel; Tamariz-Flores, J. Víctor; Castelán-Vega, Rosalía (RD-ICUAP, 2023)